Rancang Bangun Sistem Informasi Daily Reports Untuk Monitoring Kinerja Section Bushing Hunger Di PT. Aneka Komkar Utama - Rusdianto, Hengki; Damayanti, Nova Indah; Wibowo, Agung; Alamsyah, Dedy (Jurnal Teknik, 2025)
The advancement of information technology encourages companies, particularly in the manufacturing industry, to adopt digital systems in order to improve operational efficiency, including in daily production reporting. At PT Aneka Komkar Utama, especially in the production area of the Bushing Hanger section, the reporting process is still carried out manually, which makes it prone to recording errors, delays, and difficulties in data verification and analysis. This condition poses a risk of hampering performance monitoring and managerial decision-making. This study aims to design and develop an integrated and user-friendly web-based daily reporting information system using the Laravel framework. The system is designed using the Spiral model approach, which allows for iterative and gradual development through several phases: communication, planning, risk analysis, engineering, construction and deployment, and user evaluation. This approach is chosen to ensure that the system developed can flexibly adapt to user needs. The result of this research is a system capable of recording and presenting production data in real-time, thereby improving the efficiency, accuracy, and transparency of daily reports. In addition, the system provides users with the convenience of monitoring and identifying potential improvements in production performance more quickly and precisely, ultimately supporting more effective and data-driven decision-making processes.